DESIGNING A DIGITAL INNOVATION STRATEGY TO IMPROVE PERSONALIZATION AND GUEST SATISFACTION AT ARTOTEL GROUP - Yerry Herawan,; Putu Herny Susanti, (Journal of Innovation Research and Knowledge, 2025)
This article explores the development of digital innovation strategies within the hospitality sector, focusing on the ARTOTEL Group. The study aims to enhance guest personalization and satisfaction through the integration of advanced technologies such as Artificial Intelligence (AI), the Internet of Things (IoT), and data analytics. The research underscores the necessity of adopting Google Analytics 4 (GA4) by July 2025 to ensure precise and comprehensive marketing data access. Qualitative Descriptive Research Method provides a review or interpretation of the data and information obtained. The findings suggest that aligning technology with brand identity and data-driven personalization can significantly improve guest loyalty and market segmentation.